Clinical relevance of bacterial resistance in lower respiratory tract infection in primary care: secondary analysis of a multicentre European trial - Teepe, J; Broekhuizen, B; Goossens, H; Hordijk, P; Loens, K; Lammens, C; Ieven, M; Little, P; Butler, C; Coenen, S; Godycki-Cwirko, M; Henriques-Normark, B; et al. (Royal College of General Practitioners, 2018)
Background: The impact of antimicrobial resistance on clinical outcomes in patients with lower respiratory tract infection in primary care is largely unknown. Aim: To determine the illness course of infections with resistant bacteria in adults presenting to primary care with acute cough. Design and setting: Secondary analysis of a multicentre European trial in primary care. Method: A total of 2061 adults with acute cough (lasting ≤28 days) were recruited from primary care and randomised to amoxicillin or placebo. To reflect the natural course of disease, only patients in the placebo group (n = 1021) were eligible. Nasopharyngeal flocked swabs and/or sputa (when available) were analysed at baseline and Streptococcus pneumoniae and Haemophilus influenzae isolates underwent susceptibility testing. Patients recorded their symptoms in a diary every day for 4 weeks. Patients with and without resistant bacterial infection were compared with regards to symptom severity, duration of symptoms, worsening of illness, and duration of interference with normal activities or work. Results: Of the 834 patients with diary records, 104 showed S. pneumoniae and/or H. influenzae infection. Of this number, 54 (52%) were resistant to antibiotics, while seven (7%) were resistant to penicillin. For the duration of symptoms rated ‘moderately bad or worse’ (hazard ratio 1.27, 95% confidence interval [CI] = 0.67 to 2.44), mean symptom severity (difference −0.48, 95% CI = −1.17 to 0.21), and worsening of illness (odds ratio 0.31, 95% CI = 0.07 to 1.41), there was no statistically significant difference between the antibiotic-resistant and antibiotic-sensitive groups. Conclusion: The illness course of antibiotic-resistant lower respiratory tract infection does not differ from that caused by antibiotic-sensitive bacteria.